Planning and Construction of Western Region Cities of Latvia in the 18th Century - Ozola, Silvija (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2014)
Planning and construction of Western region cities of Latvia was created in the course of several centuries. Cities of the Courland Bishopric and the Livonian Order – Golding (today’s Kuldīga), Hasenpoth (today’s Aizpute), Windau (today’s Ventspils) and Piltene – developed as agglomerations. City planning by fortress was created around non-regular form market square near the crossroads of main land roads and water roads. The architectural dominant of spatial composition was fortress with chapel or chapterhouse.In the Duchy of Courland and Semigallia on 28 February, 1567 the Landtag of Courland took a decision on building of Lutheran churches, schools and hospitals. Lutheran religion was declared as official religion in the Duchy of Courlandia and Semigallia. The understanding of city architectonic spatial planning changed – the construction of centres was created nearby churches and the main spatial dominant of city construction in 17th century became a church by the market square in the site of traffic main roads’ junction. Planning and road network developed in towns, but construction was created by wooden houses, that were characteristic to rural regions. Cities became typologically different.The events of The Great Northern war at the beginning of 18th century promoted not only the improvement of city defence measures and the perfection of fortification system, but also influenced significantly the further development of cities: street and square systems of functionally different significance became important in planning. City construction, which was complemented with buildings that were for public functions, became varied.The aim of the study: to analyze the development of towns of the Duchy of Courlandia and Semigallia in 18th century, to ascertain the common and different spatial composition characteristics of planning and construction.